Pani Ula i pani prezydent. Cenzura jako mechanizm lokalnego życia teatralnego, przypadek „Nieskończonej historii” Uli Kijak w Teatrze Nowym w Zabrzu - Mrozek, Witold (Instytut im. Jerzego Grotowskiego we Wrocławiu (wydawca); Wydział Polonistyki UJ (współwydawca), 2021)
The article highlights an attempt at modifying the performance Unfished Story by Ula Kijak at the Teatr Nowy (New Theatre) in Zabrze in 2012 – after a protest by some local Catholic and right-wing activists, and also by the sponsors of the theatre. Jerzy Makselon, the managing director of the theatre, tried to organize a special non-public performance of the play with the Mayor of the City as an expert in order to decide on the future of the performance. The author of the play, Artur Pałyga, declared that the Zabrze case is just the tip of the iceberg because the problem of censorship is very present in Polish theatre, and often generates conflicts between managers and local politicians on the one side and artists on the other side. However, the strategies of censorship and mechanism of power are usually not as apparent as in Zabrze. The research approach applied in the article combines institutional analysis, legal aspects and reflection upon the social significance of the artistic phenomena described.